Management Problems of Madrasah Diniah Takmiliyah Awaliyah Rejang Lebong Old Religious Units in Memorizing Al-Qur’an Juz Amma - Murni Yanto (Nazhruna: Jurnal Pendidikan Islam, 2021)
The problem of this research is not all students have problems memorizing the Al-Qur’an, but there is some student who thinks memorizing the is a busy thing because they have prepared lessons and assignments at school, This study used qualitative descriptive method while data collection, the authors used three techniques, namely the survey technique used to find out things related to the tahfiz learning system to get data, and the interview technique was used to find information things related to the tahfiz learning system to get data, and the interview technique was used to find information from a student who took Tahfiz Al-,Qur’an, the documentation technique used to obtain information relating to completeness in the learning activities of the Al-Qur’an tahfiz that was carried out, and the data that supported this study were students and teachers of. Based on the results of the research, it can be concluded that the problem is evidence that some students who follow Tahfiz Al-Qur’an get unsatisfactory scores. This is caused by several factors such as the factor of not being able to feel the pleasure of the Qur’an, the lazy factor, the lack of motivation, the forgetting factor, the following interaction factor, the factor of not being able to read the Qur’an, the factor of not being able to manage the time.,the factor of the lack of a guidebook for memorizing the Qur’an.